A COMPARATIVE ANALYSIS: EVALUATING THE SAFETY AND FEASIBILITY OF 24/7 LAPAROSCOPIC CHOLECYSTECTOMY FOR VARIED GRADES OF CHOLECYSTITIS, SPANNING FROM MILD TO GANGRENOUS (Journal of Medical & Health Sciences Review, 2025)
Background: Acute cholecystitis is an extremely common surgical emergency, with gallbladder inflammation from mild to gangrenous forms. Early surgical intervention, often laparoscopic cholecystectomy, is required to minimize the chances of morbidity and to improve important patient outcomes. The introduction of laparoscopic services continuing 24/7 is designed to minimize surgical delays and improve care quality.Aim: The purposes of this study are to compare the safety and feasibility of laparoscopic cholecystectomy performed 24/7 for various grades of acute cholecystitis, ranging from mild to gangrenous.Methods: Four hundred patients diagnosed with acute cholecystitis were divided into three groups such as grade I (mild), grade II (moderate), and grade III (severe/gangrenous) according to the Tokyo Guidelines, and a comparative study was done. Patients were divided into two groups by simple fixed ratio allocation: one undergoing elective laparoscopic cholecystectomy during regular business hours (n = 200) or those who underwent 24/7 laparoscopic cholecystectomy (n = 200). Operative time, conversion rates to open surgery, complications rates, hospital stay duration and postoperative recovery metrics were assessed as outcomes. Chi-square tests were performed for categorical variables and t-tests for continuous variables, and a p value less than significant was taken as